2017
DOI: 10.14260/jemds/2017/799
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine Versus Bupivacaine-Lignocaine Mixture in Peribulbar Block- A Comparative Study

Abstract: BACKGROUNDRopivacaine is a newer local anaesthetic agent with low systemic side effects. It has the potential advantage of reduced cardiovascular and neurological toxicity compared with other available local anaesthetics that are commonly used for peribulbar anaesthesia. In this study, we intend to compare the efficacy of Ropivacaine as against Bupivacaine-Lignocaine mixture in peribulbar anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Similar to our study, Varshney et al 8 reported better postoperative anesthesia with ropivacaine as compared to combined lignocaine and bupivacaine. However, this study was limited only to macular surgeries, where the globe manipulation was minimal.…”
Section: Limitation Of the Studysupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our study, Varshney et al 8 reported better postoperative anesthesia with ropivacaine as compared to combined lignocaine and bupivacaine. However, this study was limited only to macular surgeries, where the globe manipulation was minimal.…”
Section: Limitation Of the Studysupporting
confidence: 91%
“…Varshney et al concluded that ropivacaine was a good alternative for peribulbar anesthesia compared to bupivacaine/lignocaine as it has a faster onset and lesser toxic effects than other comparable local anesthetic agents. 8 Peribulbar block involves the administration of local anesthetic into the muscle orbicularis oris both above and below the orbit. This technique blocks the ciliary nerves in addition to CN III and VI; however, the optic nerve remains unobstructed during this form of local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varshney et al . [ 23 ] comparing ropivacaine 0.75% with a 1:1 mixture of bupivacaine 0.5% and lidocaine 2%, reported onset of complete akinesia (motor block) as 15 min, whereas we observed the duration of the onset of motor block as 2.8 ± 1.2 min, 2.9 ± 1.2 min, 2.9 ± 1.3 min, and 2.7 ± 1.9 min, respectively, in our four groups. The faster onset of the block noted in our study clearly indicates the role of DMT and hyaluronidase used in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 ] Although the efficacy and safety of ropivacaine for peribulbar and retrobulbar anesthesia during cataract surgery have been extensively studied, data on the use of topical ropivacaine in cataract surgery are limited. [ 9 10 11 12 13 ]…”
mentioning
confidence: 99%